2022
DOI: 10.4103/2452-2473.336104
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral continuous serratus anterior plane block: An effective alternative for bilateral multiple rib fracture analgesia

Abstract: Pain due to rib fracture leads to respiratory impairment and bilateral fractures impact respiratory mechanics in the worst manner. Thoracic epidural analgesia is the gold standard for bilateral rib fractures but is technically difficult, entails potentially serious complications, and necessitates patient repositioning. Ultrasound-guided serratus anterior plane block (SAPB) has recently gained favor for alleviating thoracic pain and can be performed in patients lying supine, rendering it particularly useful in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…We provided a detailed explanation regarding the clinical study to five patients who presented to the Emergency department of the Nara Prefecture General Medical Center (Nara, Japan) between October 2022 and December 2022 with multiple rib fractures; among them, three patients provided consent to participate and were included in the study. The inclusion criteria were as follows: (1) patients aged 20-80 years, (2) chest pain due to multiple ribs fracture, (3) no alterations in the level of consciousness, and (4) ability to provide informed consent. The exclusion criteria were as follows: (1) severe infection, (2) pregnancy, (3) ventilator control, (4) severe cognitive impairment (Mini-Mental State Evaluation ≤10), ( 5) inability to answer the questionnaires, or (6) judged to be inappropriate for participation by the principal investigator or co-investigator.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We provided a detailed explanation regarding the clinical study to five patients who presented to the Emergency department of the Nara Prefecture General Medical Center (Nara, Japan) between October 2022 and December 2022 with multiple rib fractures; among them, three patients provided consent to participate and were included in the study. The inclusion criteria were as follows: (1) patients aged 20-80 years, (2) chest pain due to multiple ribs fracture, (3) no alterations in the level of consciousness, and (4) ability to provide informed consent. The exclusion criteria were as follows: (1) severe infection, (2) pregnancy, (3) ventilator control, (4) severe cognitive impairment (Mini-Mental State Evaluation ≤10), ( 5) inability to answer the questionnaires, or (6) judged to be inappropriate for participation by the principal investigator or co-investigator.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Epidural and paravertebral blocks are recommended if the analgesia is inadequate; however, pain may prevent proper positioning. Therefore, the serratus anterior fascia plane (SAP) block has attracted attention as a local anesthetic method 2 , 3 ) . Although a previous retrospective study has demonstrated the efficacy of the continue SAP block 4 ) , most patients require SAP blocks to be performed repeatedly.…”
Section: Introductionmentioning
confidence: 99%